Experimental Investigation of Self-Assembled Particles on Profile Control in the Fuyu Oilfield - Dong, Lifei; Wang, Miao; He, Jie; Ding, Mingchen; Lin, Hun (Frontiers in Chemistry, 2021)
The particle system is one of the widely used profile control agents in many oilfields, and the matching relationship between the particle and the reservoir pore throat is significant for the profile control effect. In order to enhance oil recovery after water breakthrough in Fuyu oilfield, a self-assembled particle with some branches on the surface, compounded by inverse emulsion polymerization and added, is introduced as the profile control agent in this paper. Then the permeabilities of the water channel and the oil remianed area in Fuyu oilfield are achieved after the statistic analysis of 1022 cores from the practical reservoir. Furthermore, the oil restarting pressure in the oil remianed area and the self-assembled particle plugging strength in the water channel are experimented. Finnally, the adaption of self-assembled particle and effect of profile control in Fuyu oilfield are evaluated by comparing the oil restarting pressure and the plugging strength. The results show that the self-assembled particle can be gathered together easily force by the ionic bond, which is good for water channel plugging. The permeability of water channel in Fuyu oilfield is ranging from 1000 mD to 1500 mD. The oil restarting pressure increases with the decreasing of permeability, and the increasing rate grows rapidly when it drops below 50 mD. Compared the oil restarting pressure with the plugging strength, the self-assembled particle with the diameter of 20-40μm in the water channel with the permeability of 1265.7 mD can provide the plugging strength enough to restart the remaining oil in the oil remained areas with the permeability over 3.38 mD. The matched window of the self-assembled particle is wider than the normal particle in Fuyu oilfield.